Implementasi Total Quality Management (TQM) Menuju World Class University (WCU) pada Biro Administrasi Umum Universitas Muslim Indonesia Makassar - Hafied, Hamzah (Jurnal Aplikasi Manajemen, 2013)
This research goal was to understand The Implementation of Total Quality Management (TQM)for World Class University (WCU) in The General Administration Office, Indonesian Moslem University.This research used descriptive method. The performance of research used survey study applying questionnairesto respondents. In-dept research used observation and interview on research aspects. Sources ofdata or population, in this research, were full-time staffs, the civil servants of the General AdministrationOffice, Indonesian Moslem University, 30 staffs. Data, in this research, were analyzed in two phases: (1)analysis before existing in field for data of previous study results; and (2) analysis on and after data werecollected. Analysis steps, in this research, were: (1) reduction of data, to summarize data; (2) data display(presentation of data) in tables and figures; (3) verification, to make conclusion. Data, which would beanalyzed descriptively in this research, were: (1) frequency of respondents'response to the research aspects;(2) results of observation; (3) substance of interview. For tes of hypothesis used the multiple regressionanalysis. Study results indicated that implementation of Total Quality Management (TQM) that includedby preparation class, planning class and doing class have significant impact to ascend administrationstaffs quality for World Class University (WCU).However, the implementation stage has more dominantinfluence on quality improvement of administration staff toward World Class University (WCU) as revealedin table 9, where majority (76,2%) of respondent responses indicated that in periodically formal surveyeach year to monitor and provide information about satisfaction rate for determining the improvementactions needed in implementation stage toward World Class University (WCU).